Experimental Research on Brittleness and Rockburst Proneness of Three Kinds of Hard Rocks under Uniaxial Compression - Rongchao Xu; Yiding Jin; Yumin Zhang (Advances in Civil Engineering)
Rockburst is a highly destructive geological disaster caused by excavation and unloading of hard and brittle rock mass under high geostress environment. Quantitative evaluation of rock brittleness and rockburst proneness is one of the important tasks in potential rockburst assessment. In this study, uniaxial compression and acoustic emission tests were carried out for basalt, granite, and marble, and their brittleness and rockburst proneness were quantitatively evaluated. The acoustic emission evolution characteristics of the three rocks during uniaxial compression were analyzed, and the differences of fracture mechanism of the three rocks were compared. The results show that (1) based on the brittleness evaluation index, basalt is the most brittle rock, followed by granite, and marble is the weakest; (2) based on the rockburst proneness evaluation index, combined with the macroscopic failure phenomenon and morphology of the samples, the rockburst proneness of basalt is the strongest, followed by granite, and marble is the weakest; (3) there exists a positive correlation between rockburst proneness and brittleness, and the fitting results show that they are approximately exponential; and (4) brittleness has an important influence on the rock fracture mechanism. Unlike marble, basalt and granite with strong brittleness continuously present high-energy acoustic emission signals in the stage of unstable crack propagation, and large-scale fracture events continue to occur; from the calculation results of the acoustic emission b value, the stronger the brittleness of rock, the larger the proportion of large-scale fracture events in the failure process.